Successful removal of an iatrogenic pleural foreign body—pigtail catheter, using a semi-rigid thoracoscope - Pradeep Bajad; Sourabh Pahuja; Arjun Khanna; Satyam Agarwal (The Egyptian Journal of Bronchology, 2023)
Abstract Tube thoracostomy stands as the conventional treatment for pleural diseases. Nevertheless, pigtail catheters have gained traction due to their smaller size, potentially resulting in reduced complications. Despite the enhanced safety and ease of insertion associated with pigtail catheters, it is crucial to recognize that procedural complications can arise irrespective of the drainage method employed. Complications related to small-bore pigtail catheters encompass the possibilities of dislodgment, kinking, and, though rarely, breakage. Our case serves as a reminder for medical practitioners to select appropriately sized pleural tubes based on the specific pleural condition. In this instance, we present the utilization of a semi-rigid thoracoscope to extract a broken pigtail catheter from the pleural cavity. To the best of our knowledge, this is the first case report of removing a broken pleural catheter using semi-rigid medical thoracoscopy.